The nucleotide sequence of the chick cytoplasmic beta-actin gene. - Kost, T A (1983)
The nucleotide sequence of the chick beta-actin gene was determined. The gene contains 5 introns; 4 interrupt the translated region at codons 41/42, 120/122, 267, 327/328 and a large intron occurs in the 5' untranslated region. The gene has a 97 nucleotide 5'-untranslated region and a 594 nucleotide 3'-untranslated region. A slight heterogeneity in the position of the poly A addition site exists; polyadenylation can occur at either of two positions two nucleotides apart. The gene codes for an mRNA of 1814 or 1816 nucleotides, excluding the poly(A) tail. In contrast to the chick skeletal muscle actin gene the beta-actin gene lacks the Cys codon between the initiator ATG and the codon for the N-terminal amino acid of the mature protein. In the 5' flanking DNA, 15 nucleotides downstream from the CCAAT sequence, is a tract of 25 nucleotides that is highly homologous to the sequence found in the same region of the rat beta-actin gene.